Use of pedometers in a workplace physical activity program - Shaw, G.; Alfonso, Helman; Howat, Peter; Corben, Kirsten (Australasian Podiatry Council, 2007)
Hot Steppers is a pedometer-walking program developed for staff at Caulfield General Medical Centre (CGMC) in Melbourne, following a felt need expressed by staff that a physical activity program was required within the workplace. Participants were asked to complete a questionnaire adapted from the Active Australia survey at an introductory session. They were then asked to record the number of steps taken each day in a log book provided and to return it to the program coordinator at the end of each month in order to receive their log for the next month. After three months the participants were re-issued with the adapted Active Australia survey along with a process evaluation questionnaire. The evaluation enabled the coordinators to make a number of recommendations to improve the design of the program and also helped to identify a number of barriers and enablers to participation in physical activity for this group of people. This pilot program provides examples for podiatrists of how to implement a walking program using minimal resources; the use of pedometers for motivation; record keeping and evaluation; and an example of a simple and practical evaluation of a health promotion program.